مقاومة الثنائيات الليزيرية GaAs/GaAlAs من نوع فكسل (VCSELs) للإشعاعات - جبور جبور; زازوي م; بورغوان ج.ك.; جيرارد و (Latakia University Journal -Basic Sciences Series, 2018)
A series of electron irradiations of GaAs/GaAlAs Vertical Cavity Surface Emitting Lasers (VCSELs), containing several GaAs quantum wells, has been carried out for the purpose of assessing the suitability of these devices for space applications. The irradiations were performed at energy of 1 MeV. Current versus voltage (I-V) and Light intensity versus current (Light intensity-I) characteristics were measured before and after each irradiation step. The current threshold of VCSEL is shown to be the only important parameter modified by a high fluence irradiation. Changes in the threshold current show radiation generated recombination centers to be the main cause of degradation. This study will allow to understand why quantum well structures based Lasers or Laser Emitting Detectors (LEDs) are more radiation resistante than those which use a classical junction as active layer. It will also allow to predict simply the degradation induced by proton and (or) electron irradiations for any device based on such structures. <!–[if gte mso 9]> 800x600 <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; –> <!–[endif] –> تم تعريض ثنائيات (ديودات) ليزيرية من نوع (VCSELs) مصنوعة من GaAs/GaAlAs، حيث تعتمد في تركيبها على الآبار (الحفر) الكوانتية ، لسلسة من الإشعاعات الإلكترونية، وذلك لمعرفة مدى مقاومتها لهذه الإشعاعات عند استخدامها في التطبيقات الفضائية (على سبيل المثال في الأقمار الاصطناعية والمركبات الفضائية). إن طاقة هذه الإشعاعات كانت 1 ميغا إلكترون فولط (1MeV). لقد تم قياس تغير التيار بتابعية الكمون (الجهد) المطبق على هذه الثنائيات (I-V)، وشدة الضوء الصادر عن هذه الثنائيات بتابعية التيار (Light intensity-I) وذلك قبل وبعد تعرض هذه الثنائيات للإشعاعات. لقد تبين أن تيار العتبة هو أهم مقدار يتغير نتجية زيادة مقدار جرعة الإشعاعات التي تتعرض لها هذه الثنائيات. ولاحظنا أن السبب الأساسي في تلف هذه الثنائيات يتمثل بتغير تيار العتبة الذي سببه تولد مراكز إعادة ارتباط. إن هذه الدراسة سمحت بفهم آلية عمل هذا النوع من الثنائيات، وتم استنتاج أن هذه الثنائيات أكثر مقاومة للإشعاعات وأكثر فعالية (خاصة بالنسبة لتيار الإصدار الضوئي) من الثنائيات الكلاسيكية (التي لا تعتمد في تركيبها على الآبار الكوانتية). وأيضاً، فإن هذه الدراسة تسمح بالتوقع والتنبؤ بنسبة تلف أي نوع من العناصر الإلكترونية التي تعتمد في تركيبها على الآبار الكوانتية، في حال تعرضها لإشعاعات كالإلكترونات والبروتونات.